Prolegomnena for an interpretation of the documentary short film "Buscando el azul" - Cornejo Quesada, Carlos (2018)
Some elements are proposed for the interpretation of the content of the documentary short films produced by Fernando Valdivia, particularly Buscando el azul (2003), situating it on the stage of the Bora tribe. This study resorted to a qualitative methodology of basic, ethnographic and non-experimental nature, taking into account the techniques for the collection of empirical data, such as the interview, the textual stylistics (subject, subject, argument), the point of view; and the procedures (written textuality signings). This methodological instrument allowed making similarities and homologations of the content of the film and the tribal community, circumscribed to the Peruvian Amazonian universe, obtaining some thematic features that help to understand and explain the audiovisual sources.